The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0074-02762006001000011
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of tuberculosis in the Americas: how can modern biomedicine inform the ancient past?

Abstract: Tuberculosis (TB) is an infectious disease that continues to take its toll on human lives. Paleopathological research indicates that it has been a significant cause of death among humans for at least five thousand years. Because of the devastating consequences to human health, social systems, and endangered primate species, TB has been the subject of many and varied research efforts throughout the world, efforts that are amassing an enormous amount of data concerning the causative agent Mycobacterium tuberculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Studies of single nucleotide polymorphisms of Mycobacterium leprae have suggested that leprosy originated in Africa and that the Hansen disease cases in the Americas are from European and African descendants as a result of emigration and the slave trade (11). Even though molecular evidence of the presence of M. tuberculosis in the pre-Colombian age has been reported (19,25), controversy over this issue remains. If tuberculosis existed in native populations, the prevalence of specific spoligotypes would shrink significantly, since the population of about 22 million people living in Mesoamerica in 1520 was reduced by 95% by 1600, mainly because of infectious diseases (1).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of single nucleotide polymorphisms of Mycobacterium leprae have suggested that leprosy originated in Africa and that the Hansen disease cases in the Americas are from European and African descendants as a result of emigration and the slave trade (11). Even though molecular evidence of the presence of M. tuberculosis in the pre-Colombian age has been reported (19,25), controversy over this issue remains. If tuberculosis existed in native populations, the prevalence of specific spoligotypes would shrink significantly, since the population of about 22 million people living in Mesoamerica in 1520 was reduced by 95% by 1600, mainly because of infectious diseases (1).…”
Section: Discussionmentioning
confidence: 99%
“…As described by Wilbur and Buikstra [71], social disruption, forced mobility, crowding onto reservations, poor sanitation, extreme poverty, and malnutrition, with frequent exposure to pathogens, contributed to TB as a population-wide health problem. This was the case with the Tenetehara-Guajajara people since the 18th century.…”
Section: Resultsmentioning
confidence: 99%
“…One cause of criba orbitaria is iron deficiency anaemia, and in severe cases this enhances the virulence of MTB infection (Ratledge 2004). It has been suggested that the iron status within pre-Columbian populations in the Americas may have had a profound impact on the clinical presentation of the disease (Wilbur and Buikstra 2006). Work is just starting on the impact of neoplastic disease, but tuberculosis infection has been detected in an infant with Langerhans cell histiocytosis from the Vác mummy study group .…”
Section: Lowered Host Resistance or Increased Susceptibilitymentioning
confidence: 99%